Wound Grade–Associated Microbiome Diversity in Diabetic Ulcers: A Metagenomic Analysis - Andi Ernawati; Iman Rusmana; Aris Tri Wahyudi; Sri Murtini; Sri Budiarti (Pandawa Institute, 2026)
The wound's microbiome in patients with diabetes plays a vital role for developing of diabetic ulcers. Molecular sequencing technologies have enhanced our understanding of microbial diversity in diabetic wounds, making microbiome profiling analysis essential for supporting effective clinical management. A metagenomic approach enables the more accurate identification of pathogenic bacteria to support rational antibiotic use and the development of more targeted therapies. This study aimed to identify the bacterial diversity in diabetic ulcers before and after antibiotic therapy using a metagenomic approach to analyze changes in the microbiome profile and detect potentially antibiotic-resistant pathogenic bacteria. Wound swabs from each patient were genomically extracted for metagenomic analysis using nanopore sequencing. The samples from individuals administered antibiotics were coded 4, 7AB, and 8, whereas the samples from patients not administered antibiotics were coded 11. Limitations of this study include its relatively small sample size (n = 4). This study shows that the species with the highest abundance in sample 11 was Acinetobacter junii, in sample 4 was Proteus mirabilis, in sample 7AB were Alcaligenes faecalis and Pseudomonas aeruginosa, and in sample 8 was Acinetobacter baumannii. Both groups who did not receive antibiotic treatment and those who received antibiotic therapy showed the presence of diverse microorganisms, including potentially pathogenic bacteria. Future treatment regimens should be based on the type of bacterial infection in wounds of diabetic patients.